1992
DOI: 10.1080/00039896.1992.9938346
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence Following Chlorophenol Exposure in a Community in Southern Finland

Abstract: Chlorophenols have contaminated the drinking water system and the local lake in the village of Järvelä in southern Finland. Local geology, ground water streams, and chemical analyses incriminated a local sawmill as the only plausible source of exposure. Cancer incidence in the municipality of Kärkölä (half of the population lives in Järvelä), compared with the rest of the local health-care district and with the greater cancer control region, indicated an excess of soft-tissue sarcomas and non-Hodgkin's lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…Similarly diverse applications have been seen in studies of water pollution ( e.g., Baker et al, 1978;Lebowitz et al, 1992;Rao et al, 1995 ) and hazardous waste (e.g., Lagakos et al, 1986;Lampi et al, 1992;Gamble and Lewis, 1996;Molholland et al, 1998 ). Exposure indicators using residence location are easy and inexpensive to construct, and increased use is anticipated given advances in geographic information systems (GIS ) and databases that simplify identification of potentially polluted areas (Clark et al, 1982;Budnick et al, 1984;Geschwind et al, 1992;Dayal et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly diverse applications have been seen in studies of water pollution ( e.g., Baker et al, 1978;Lebowitz et al, 1992;Rao et al, 1995 ) and hazardous waste (e.g., Lagakos et al, 1986;Lampi et al, 1992;Gamble and Lewis, 1996;Molholland et al, 1998 ). Exposure indicators using residence location are easy and inexpensive to construct, and increased use is anticipated given advances in geographic information systems (GIS ) and databases that simplify identification of potentially polluted areas (Clark et al, 1982;Budnick et al, 1984;Geschwind et al, 1992;Dayal et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent population-based case-control study was conducted in the same geographical area, and an OR of 2.3 (95% CI: 1.4-3.8) was reported for individuals in the high dioxin exposure category. 163 Lampi et al 135 reported a significantly positive association with NHL risk in a Finnish community whose water system was contaminated with chlorophenols (RR 5 2.8, 95% CI: 1.4-5.6). Individual exposure measurements were not available in these studies.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%
“…The observed and expected numbers of cancer in the Kärkölä municipality were obtained for three periods These are the same cancers that were included in the first study on the chlorophenol-exposure episode in Kärkölä (6). The expected numbers were based on the gender-, age-, and calendar-year-specific cancer incidence rates in the Tampere cancer control region (1.2 million inhabitants), to which the Kärkölä municipality belongs.…”
Section: Methodsmentioning
confidence: 99%
“…A two-part investigation of cancer risk in Kärkölä was conducted immediately after the population exposure with chlorophenols was confirmed (6). An ecological analysis at the municipality level revealed that the incidence of soft-tissue cancer and non-Hodgkin's Lampi et al lymphoma in the municipality of Kärkölä was significantly higher than in the rest of the cancer-control region.…”
mentioning
confidence: 99%